Gauging the dynamic interlinkage among robotics, artificial intelligence, and green crypto investment: A quantile VAR approach - Le Thanh Ha (Borsa Istanbul Review)
A large amount of new green crypto investment is required to achieve the United Nations’ sustainable development goals. The development and application of artificial intelligence (AI) are essential for attracting this investment because it has the potential to increase the adoption of environmental innovation and individual environmental awareness. In our research, we use a DCC-GARCH copula model to examine time-varying spillover effects and demonstrate interconnections between the development of AI and green cryptocurrencies from January 1, 2018, to September 8, 2023. Our results show that when we consider the full data sample, the variables studied all have only weak connections. These results clearly demonstrate temporal variance in systemic connection caused by the COVID-19 pandemic, the Russia-Ukraine war, and bank failures. Robotics & AI ETF (BOTZ) is a net recipient of shocks across quantiles throughout the study, according to the total net directional connectivity across quantiles. Pairwise directional connectivity in an evolving net indicates that BOTZ consistently appears to be dominated by green cryptocurrencies in both the short and long term. Understanding the primary sources of spillovers between AI and green cryptocurrencies can help policymakers design the most effective strategies for mitigating these vulnerabilities and reducing market risk.